Studi Histologi Tingkat Kematangan Gonad Jantan dan Betina Bulu Babi Diadema setosum di Pulau Panjang Jepara - Evi Lutfiyani; Delianis Pringgenies; Hadi Endrawati (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2021)
The gonads maturity level (TKG) is a particular stage gonadal development before and after the spawning biota. This research aims to determine the gonads index of the Diadema setosum and the gonads maturity level of Diadema setosum found on Panjang Island, Jepara. The research method used was the observation method. The gonads histology was made by using paraffin method and hematoxylin-eosin staining. The measured parameters were the diameter of the shell, the Gonads Maturity Index (GI) and the Gonads Maturity Level, and environmental parameters such as temperature, pH, DO, and salinity of the water. The Gonads Maturity Level was determined on the histology of gonads. The result shows average Diadema setosum GI value of 7,334 % with an optimum maturity in December. Based on the height of individual the sea urchin (Diadema setosum) found in the category TKG III, which is 11 out of 30 Individuals and two individuals in the TKG IV category are observed histology of the gonadal showing in that phase.